Metawriting: Empowering students to discover their knowledge of writing - Madeleine Mejia (Journal of Pedagogical Research, 2023)
This qualitative study investigated the influence of Metawriting, or "writing about writing," on fifth-grade students' knowledge of writing and proficiency in composing informative essays. Using a Think-Talk-Write model, students explored their existing writing knowledge and experiences, analyzed their essays using genre-specific tools, and discussed their insights with peers. Students kept a Metawriting journal to document their self-assessment experiences, capture their observations and create writing goals. An analysis of the data revealed that the iterative process of the Think-Talk-Write model to teach Metawriting guides students through well-defined stages, enhancing their metacognitive declarative, procedural, and conditional knowledge of writing. By thinking, talking, and writing about their writing, students became more aware of who they are in the writing process, enhanced their knowledge of informative text structures, and exhibited increased self-regulatory skills.